Antecedents of psychological empowerment in the Malaysian private higher education institutions. - Abd. Ghani, Nik Azida; Raja Hussin, Tengku Ahmad Badrul Shah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Psychological empowerment comprising four cognitive dimensions i.e. meaning, competence, autonomy and impact in the context of private higher education institutions is being validated. Five factors considered as antecedents i.e. access to information, resources, organizational support and opportunity to learn and develop, and trust were studied. This study examined on a sample of 312 lecturers from 25 private higher education institutions in three states (Penang, Kedah and Kelantan) in Malaysia. Survey data was analyzed using correlation and regression analyses to assess the relationship among the factors as well as the contribution of each factor to psychological empowerment. The study verifies that psychological empowerment comprised four dimensions as suggested by Spreitzer (1992). The results indicated that all antecedents under study have significant relationship with psychological empowerment at .01 significance level. It has also been found that access to opportunity to learn and develop and access to resources are significant predictors of psychological empowerment. It is recommended that management of higher education institutions use these findings to improve the level of psychological empowerment of lecturers.